Much More than a Cardiotonic Steroid: Modulation of Inflammation by Ouabain - Cavalcante-Silva, Luiz H. A.; Lima, Éssia de Almeida; Carvalho, Deyse C. M.; Sales-Neto, José M. de; Alves, Anne K. de Abreu; Galvão, José G. F. M.; Silva, Juliane S. de França da; Rodrigues-Mascarenhas, Sandra (Frontiers in Physiology, 2017)
Since the discovery of ouabain as a cardiotonic steroid hormone present in higher mammals, research about it has progressed rapidly and several of its physiological and pharmacological effects have been described. Ouabain can behave as a stress hormone and adrenal cortex is its main source. Direct effects of ouabain are originated due to the binding to its receptor, the Na+/K+-ATPase, on target cells. This interaction can promote Na+ transport blockade or even activation of signaling transduction pathways (e.g., EGFR/Src-Ras-ERK pathway activation), independent of ion transport. Besides the well-known effect of ouabain on the cardiovascular system and blood pressure control, compelling evidence indicates that ouabain regulates a number of immune functions. Inflammation is a tightly coordinated immunological function that is also affected by ouabain. Indeed, this hormone can modulate many inflammatory events such as cell migration, vascular permeability, and cytokine production. Moreover, ouabain also interferes on neuroinflammation. However, it is not clear how ouabain controls these events. In this brief review, we summarize the updates of ouabain effect on several aspects of peripheral and central inflammation, bringing new insights into ouabain functions on the immune system.